COMMUNICATIVE LANGUAGE TEACHING IN ENGLISH LANGUAGE TEACHING METHODOLOGY - Choriyev Botir,; Norqobilov Quddus, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Communicative  Language  Teaching  (CLT)  is  one  of  the  most  influential approaches in modern language education. It emphasizes the ability to use language for  meaningful  communication  rather  than  only  memorizing  grammar  rules.  This article  discusses  the  main  principles  of  CLT,  its  historical  background,  classroom procedures,  advantages,  and  possible  limitations.  The  paper  also  shows  why  CLT remains  important  in  English  language  teaching  today.  The  analysis  is  based  on  a review of methodological literature and on the practical needs of language learners who must develop communicative competence in real-life situations.